The Psychological and Emotional Impact of Sudden Parental Death on Children’s Grief - Adaobi Jennifer Iloakasia; Denata Viana da Conceicão (International Journal of Counseling and Psychotherapy, 2025)
Background: The sudden death of a parent is a deeply traumatic event for children, often causing significant emotional and psychological disruptions that hinder their development and academic performance. Objective: This study investigated the psychological and emotional impacts of sudden parental death on children. Method: Using a descriptive survey design, data were collected through the validated Sudden Parental Death Impact Assessment Questionnaire (SPDIQ), with high internal consistency (α = 0.85, 0.72, 0.81). SPSS v25 was used to analyze responses via descriptive statistics, ANOVA, and Pearson correlation. Results: Findings showed that emotional shock, isolation, fear, and suicidal thoughts were among the most reported effects, along with depression and academic decline. Moderate, statistically significant correlations existed between sudden parental death and both emotional and psychological distress. Conclusion: The study confirms that sudden parental death has a measurable and distressing impact on children, irrespective of the background of the supporting counselor. Contribution: This research contributes empirical evidence to child grief literature by quantifying the emotional and psychological effects of sudden bereavement while also challenging prevailing assumptions about counselor effectiveness.